Penelusuran Pustaka Potensi Genus Camellia sebagai Antikanker - Salma Azizah; Kiki Mulkiya Yuliawati; Indra Topik Maulana (Bandung Conference Series: Pharmacy, 2022)
Abstract. Cancer is the third most common cause of death in Indonesia after heart disease and stroke. One of the causes of cancer is the presence of excess free radicals in the body. Antioxidants are compounds that can counteract free radicals in the body. Antioxidants are plant activities produced by compounds such as phenols, polyphenols, flavonoids, vitamins C and E, catechins and carotenes. It has been studied phytochemically that the genus Camellia contains compounds such as tannins, alkoloids, terpenoids, flavonoids and other phenolics. Antioxidants have been shown to be beneficial in the prevention of cancer cells. Based on the antioxidant chemical content in plants of the Camellia genus, this literature search was carried out with the aim of knowing, collecting information and analyzing whether the Camellia genus has potential as an anticancer. And any type of cancer cells whose growth can be inhibited by the genus Camellia. There are 5 species of plants from the Camellia genus that have antioxidant and anticancer activities. Based on the literature search, several studies have proven that plants of the Camellia genus have antioxidant and anticancer activities with the identified compounds being phenol derivative compounds and genus Camellia can inhibit breast cancer cells MCF-7, MDA-MB-231, and prostate cancer PC3. Abstrak. Kanker merupakan penyakit penyebab kematian ketiga terbanyak di Indonesia setelah jantung dan stroke. Salah satu penyebab kanker yaitu adanya radikal bebas berlebih yang ada ditubuh. Antioksidan adalah suatu senyawa yang dapat menangkal radikal bebas didalam tubuh. Antioksidan adalah aktivitas tanaman yang dihasilkan oleh suatu senyawa seperti fenol, polifenol, flavonoid, vitamin C dan E, katekin dan karoten. Telah dipelajari secara fitokimia bahwa genus Camellia mempunyai kandungan senyawa seperti tanin, alkoloid, terpenoid, flavonoid dan fenolat lainnya. Antioksidan sudah terbukti bermanfaat dalam pencegahan sel kanker. Berdasarkan kandungan kimia antioksidan dalam tanaman genus Camelliadilakukan penelusuran pustaka ini bertujuan untuk mengetahui, mengumpulkan informasi dan menganalisis apakah genus Camellia memiliki potensi sebagai antikanker. Dan jenis sel kanker apa saja yang pertumbuhannya dapat dihambat oleh genus Camellia. Terdapat 5 spesies tanaman dari genus Camellia yang memiliki aktivitas antioksidan dan antikanker. Berdasarkan penelusuran pustaka bahwa beberapa penelitian membuktikan tanaman dari genus Camellia memiliki aktivitas antioksidan dan antikanker dengan senyawa yang teridentifikasi yaitu senyawa turunan fenol.. dan genus Camellia dapat menghambat sel kanker payudara MCF-7, MDA- MB-231, dan kanker prostat PC3.